Staff Studies for the World Economic Outlook. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1995)
These studies, prepared by the staff of the International Monetary Fund, comprise supporting material for the analyses and scenarios in the World Economic Outlook and provide a more detailed examination of the theory and evidence on some major issues affecting the global economy, commodity prices, and individual countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet